STUDI BIOEKOLOGI PERAIRAN SUNGAI BATU BATU DAN SUNGAI WALANAE UNTUK MENDUKUNG KEGIATAN BUDIDAYA DI DANAU TEMPE KAB.SOPPENG DAN WAJO PROP.SULAWESI SELATAN (Torani Journal of Fisheries and Marine Science, 2017)
Study aim was to determine bioecology aspect of Batu-Batu and Walanae River for supporting aquacultureacitivies at Tempe Lake. Batu-Batu and Walanae Rivers were 2 out of 8 river where affected water quality ofTempe Lake. Research was conducted for 7 months and sampling was conducted for 5 times. Physical waterquality parameters were measured in situ while chemical, primary productivity and nutrients parameterswere analysed at laboratorium. Results showed that range of temperature and pH were 30.5 – 31.7oC and7.49 – 7.90, respectively. Range of phytoplankton and zooplankton abundance account for 512 – 2220 cell/Land 40 – 140 ind/L, repectively. Consentration nitrate was range 0.0015 – 0.0452 mg/L, while consentrationphosphate was range of 0.015 – 0.1340 mg/L Chlorophyll a concentration was range 0.007 – 2.550 mg/Land primary productivity had range account for 0.10 – 0.89. Based on water quality parameter concludedthat Batu-Batu and Walanae River had a significant effect on abundance of phytoplankton and primaryproductivity. Phosphate and nitrate concentration significantly affected on growth of phytoplankton andzooplankton, so this could be supported for aquaculture activities.